Potentially inadequate medications in elderly people of los Guidos-Costa Rica, 2018 - Jiménez, Luis A. (2018)
Elderly people due to their physical and mental conditions, receive medications with the intention of improving their quality of life but it is not always right. Methodology: the objective of this observational and descriptive study was to identify potentially inappropriate medications in elderly people older than 65 years of Los Guidos de Desamparados, San José, Costa Rica; based on the application of the Beers-STOPP-START criteria. We visited the home of 143 people, 99 (69%) women and 44 (31%) men. Results: 1.319 cases of medications were found 31.796 units, especially in tablets (79%), 70% of people kept them in the bedroom, 71% came from Social Security, 612 cases (46,3%) had less than six months of permanence at home and 225 (17%) cases got expired date; the cases of medications are to treat affections of the cardiovascular (29%), digestive (22%) and skeletal muscle (12%) system; 78,64% of the elderly presented polypharmacy (>5 medicines) and 71% had at least one potentially inappropriate medication, highlighting furosemide (18 cases), amlodipine (15 cases), atenolol (14 cases), enalapril (11 cases), irbesartan (6 cases), famotidine (35 cases), omeprazole (18 cases), lovastatin (7 cases), metoclopramide (7 cases), hyoscine butyl bromide (7 cases), ibuprofen (31 cases), sulindac (12 cases), indomethacin (9 cases), fluoxetine (18 cases), amitriptyline (12 cases) and chlorpheniramine (9 cases). Conclusions: the particular conditions of the elderly are combined in a negative way with the large number of medicines available at home, which can potentially generate adverse reactions or expire at home. Interventions are required for a rational use of medicines that improve the quality of life of the elderly.